Trachoma: Blinding Tropical Disease in the South East Asia Region with Research Priority - Amin, Mohammad Robed; Basher, Ariful; Hawlader, Anisur Rahaman; Faiz, MA (Journal of Medicine, 2011)
DOI: 10.3329/jom.v12i1.6338 J Medicine 2011; 12 : 50-54